2021
DOI: 10.1055/s-0041-1729158
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Morbidity after Cesarean Delivery for Active Phase Arrest following Adoption of the Obstetric Care Consensus Guidelines

Abstract: Objective In an effort to reduce the primary cesarean delivery (CD) rate, the American College of Obstetricians and Gynecologists (ACOG) recommended new labor guidelines in 2014 that allow longer duration of labor times. There are little data on the impact of these guidelines on CD rates and pregnancy outcomes in a predominantly Hispanic population. This study aimed to compare the primary CD rates and maternal and neonatal outcomes in patients undergoing primary CD for arrest of labor before and after implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…1 Due to this drastic change in the new era, the complex surgical difficulties faced by an obstetrician has become a dilemma. 2 The overwhelming work at tertiary care centres is making the trainees and obstetricians' life strenuous. The leap seen in placenta accreta spectrum (PAS), rupture uterus and obstetrical hysterectomies has raised maternal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to this drastic change in the new era, the complex surgical difficulties faced by an obstetrician has become a dilemma. 2 The overwhelming work at tertiary care centres is making the trainees and obstetricians' life strenuous. The leap seen in placenta accreta spectrum (PAS), rupture uterus and obstetrical hysterectomies has raised maternal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…After studies not relevant to the subject of interest and meeting abstracts were eliminated, nine were retrieved for complete analysis. 5,6,8,[21][22][23][24][25][26] Two studies were excluded: one for including only pregnant women who had a cesarean delivery 21 and one because of the inability to determine from published information the number of cesarean deliveries performed in the second stage of labor. 22 The corresponding author for the latter study was contacted and indicated that they could not provide the additional information requested.…”
Section: Resultsmentioning
confidence: 99%